Candidate Species for Florida Aquaculture: Gulf Killifish, Fundulus grandis - Shane W. Ramee; Joshua T. Patterson; Cortney L. Ohs; Matthew DiMaggio (EDIS)
The Gulf killifish is a promising species for commercial aquaculture in Florida with the potential to help diversify the marine baitfish aquaculture industry in Florida and throughout the southeastern United States. Methods for culturing this species have improved in the past decade. This 6-page fact sheet describes the new methods and some strategies to give producers greater control of reproduction, larval growth, and survival. The publication provides the information producers need to make the most informed decision possible when considering Gulf killifish aquaculture. Written by Shane W. Ramee, Joshua T. Patterson, Cortney L. Ohs, and Matthew A. DiMaggio, and published by the Program in Fisheries and Aquatic Sciences, School of Forest Resources and Conservation, January 2016.